Targeted SPION siderophore conjugate loaded with doxorubicin as a theranostic agent for imaging and treatment of colon carcinoma - Rahim Nosrati (Nature Portfolio, 2021)
Abstract Recently, the siderophores have opened new horizons in nanomedicine. The current study aimed to design a theranostic platform based on superparamagnetic iron oxide nanoparticles-pyoverdine (SPION/PVD) conjugates bound to MUC1 aptamer (MUC1Apt) and loaded with doxorubicin (DOX) as an anti-cancer agent. The SPION/PVD complex was covalently conjugated to MUC1Apt and loaded with DOX to prepare a targeted drug delivery system (SPION/PVD/MUC1Apt/DOX). The investigation of cellular cytotoxicity and uptake of formulations by MTT and flow cytometry in both MUC1 positive (C26) and MUC1 negative (CHO) cell lines revealed that MUC1Apt could improve both cellular uptake and toxicity in the C26 cell line. The evaluation of tumor-targeting activity by in vivo bio-distribution showed that the targeted formulation could enhance tumor inhibitory growth effect and survival rate in C26 tumor-bearing mice. Furthermore, the potential of synthesized SPION/PVD/MUC1Apt/DOX complex as diagnostic agents was investigated by magnetic resonance imaging (MRI) which improved the contrast of tumor site in MRI. Our findings confirm that aptamer-targeted PVD chelated the SPION as a diagnostic agent and loaded with DOX as a chemotherapeutic drug, would be beneficial as a novel theranostic platform.